Hubungan Kondisi Fisik Dan Pengetahuan Ibu Hamil Primigravida Dengan Aktivitas Seksual Wilayah Kerja Puskesmas Darussalam Kabupaten Aceh Besar - Rosalinda, Rosalinda; Malem, Rehmaita; Rahmisyah, Rahmisyah; Riza, Nelva (Teewan Journal Solutions, 2024)
During pregnancy, physical and psychosocial changes occur due to the growth and development of the fetus. During pregnancy, it is estimated that 80% of physical and psychological changes occur in pregnant women. Thisstudy is tofind out the relationship between the physical condition and knowledge of primigravida pregnant women with sexual activity. This type of research is cross sectional. The population in this study is all primigravida pregnant women in the Working Area of the Darussalam Health Center, Aceh Besar Regency in July 2024 as many as 34 people by means of total sampling. This research was conducted in July 2024 with a questionnaire filling method. Data processing is carried out using a chi square test. The results of the univariate analysis revealedthat the majority of physical conditions in primigravida pregnant women in the Darussalam Health Center Working Area, Aceh Besar Regency in 2024, were in the sick category , which was 58.8%, the majority of knowledge of primigravida pregnant women is in the poor category, which is 58.8% and the majority of sexual activity in primigravida pregnant women is in the declining category , which is 70.6%. Theresults of bivariate analysis obtained ada relationship between physical conditions p value (0.002 < α : 0.05, ada relationship between knowledge p value (0.000 < α : 0.05 ) primigravida pregnant women with sexual activity. It is expected that respondents will deepen their knowledge about sexual activity during pregnancy both through print and electronic media.